Diagnosis and treatment of leprous neuropathy: a review - Thiodorus, Fira; Thiodorus, Robert; Sadeli, Marrietta Sugiarti (Bali Dermatology Venereology and Aesthetic Journal, 2024)
One significant subset of curable neuropathies brought on by Mycobacterium leprae is leprous neuropathy. Millions of people in most underdeveloped nations suffer from leprous neuropathy, which can lead to debilitating motor deficiencies, sensory loss, and skin deterioration. The peripheral nerve system and skin are the primary organs affected by leprosy. The clinical characteristics, cutaneous histology, and bacteriology may all be used to conclude the diagnosis. Leprosy neuropathy diagnosis also requires a nerve biopsy. Needles electromyography and nerve conduction investigations are two examples of electrophysiologic nerve examinations. Both studies offer details on the degree of nerve involvement, the location of lesions, and the underlying mechanism of injury. For patients with leprosy neuropathy, multiple medication therapies are recommended. Aside from standard medical care, acute neuropathy may sometimes require surgical intervention. In reversal reactions, corticosteroids can prevent or lessen nerve damage.